Pengaruh Capital Adequacy Ratio Dan Loan to Deposit Ratio Terhadap Harga Saham Pada PT. Bank Jago, Tbk. - Aprilya, Syarfika; Afriyani, Afriyani (LPPM STIE Tri Dharma Nusantara - Makassar, 2024)
The purpose of this research is to determine the influence of the Capital Adequacy Ratio and Loan to Deposit Ratio on share prices at PT. Jago Bank, Tbk. The type of data used in this research is quantitative data, the data source used is secondary data. The analytical methods used are descriptive methods and linear multiple regression analysis, coefficient of determination, correlation coefficient, t test and f test. Research results of the regression equation Y= -10,479.907 + 61.477X1 + 97.523X2 + e. Simultaneously, the influence is not significant on the variables Capital Adequacy Ratio and Loan to Deposit Ratio on share prices at PT. Jago Bank, tbk. The Capital Adequacy Ratio has a positive and insignificant effect on the share price at PT. Jago Bank, tbk.